Patient-reported outcome measures in patients with familial cerebral cavernous malformations: results from the Treat_CCM trial - Jennifer M. T. A. Meessen; Giorgia Abete-Fornara; Barbara Zarino; Marco Castori; Laura Tassi; Maria R. Carriero; Q. G. D'Alessandris; R. Al-Shahi Salman; Adriana Blanda; Enrico B. Nicolis; Deborah Novelli; Maria Caruana; et al. (Frontiers in Neurology, 2024)
BackgroundThe Phase 1/2 Treat_CCM randomized controlled trial for people with familial cerebral cavernous malformations (FCCMs) confirmed the safety of propranolol and suggested beneficial effects on intracerebral hemorrhage or new focal neurological deficits, but the effects on patient-reported outcome measures have not been reported.MethodsParticipants completed self-reported questionnaires at baseline, 1 and 2 years. Depression was assessed with the Beck Depression Inventory-II (BDI-2); Anxiety with the State–Trait Anxiety Inventory X1 and X2 (STAI X-1 and STAI X-2); and Quality of Life with the Short Form 36 (SF-36), split into the physical and mental component scales (PCS and MCS). Differences between treatment groups and the general population were assessed. Change over time by treatment was assessed by means of mixed models.ResultsIn total, 71 participants (48 propranolol and 23 standard care) were enrolled, of whom 61 (73%) completed questionnaires at baseline and 2-year FU. At baseline, no differences between treatment groups for any of the questionnaires were present. Twenty (31.7%) patients were considered depressed at baseline, while this proportion was lower in the propranolol group after 2 years (28.6% vs. 55.5%, p = 0.047). The STAI X-1 and X-2 scores were stable over time. PCS was lower in FCCM patients as compared with the general Italian population, while the MCS was similar to the general population. No effect of propranolol was found for both PCS and MCS.ConclusionDepression is common among patients with FCCM. Patients randomized to propranolol had a lower proportion of participants with depression after 2 years.Clinical trial registration: https://clinicaltrials.gov/, identifier (NCT03589014).